Preparation method of composite current collector for low-temperature lithium ion battery capable of rapidly discharging at low temperature

By using composite liquid collectors prepared by porous polymers in lithium-ion batteries, the problem of ion electron conduction imbalance in the electrode at low temperatures is solved, high magnification and extremely low temperature discharge capabilities are achieved, battery life is extended and battery lightness is achieved Quantification and high energy density.

CN119287469AActive Publication Date: 2025-01-10HEILONGJIANG ELECTRIC POWER SCIENCE RESEARCH INSTITUTE +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411353137.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-10
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

At low temperature, lithium-ion batteries have insufficient discharge capacity due to unbalanced ion electron conduction in the electrode, which limits their use in cold energy storage and low-altitude drones.

Method used

Porous polymers are used to prepare composite current collectors, with aluminum or copper layers on both sides, as current collectors for electrodes, absorb and store electrolytes, provide ion sources, achieve ion electron balance, and improve the battery's low-temperature and high-current discharge capacity.

Benefits of technology

The high-rate discharge and extremely low-temperature discharge effects are achieved at low temperatures, which alleviates the ion-electron conductance imbalance problem inside the electrode, extends the battery life and realizes the lightweight and high energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287469A_ABST
    Figure CN119287469A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a composite current collector for a low-lithium ion battery capable of rapidly discharging at low temperature. The method comprises the following steps: step 1, preparing a porous polymer substrate; step 2, preparing a metal-based pre-impregnation liquid; and 3, preparing the porous composite metal current collector. The middle layer of the composite current collector prepared by the method is composed of the porous polymer, the two sides of the middle layer are plated with the aluminum metal layer or the copper layer and used for a positive electrode and a negative electrode respectively, the porous current collector replaces a traditional metal current collector and can absorb and store a certain amount of electrolyte, and therefore an ion source is provided on one side of the current collector, ion-electron balance is achieved, and the service life of the current collector is prolonged. And the effect of high discharge capacity of the battery under low-temperature large current is achieved. Compared with a conventional metal current collector, the porous composite current collector prepared by the invention is lighter in weight, is beneficial to light weight of a battery, realizes the battery with higher energy density, and can relieve attenuation caused by electrolyte dryness and prolong the service life of the battery due to the capability of storing the electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a method for preparing a current collector, and in particular to a method for preparing a composite current collector for a low-lithium ion battery capable of rapid discharge at low temperature. Background Art

[0002] Lithium-ion batteries have been applied to battery cars, portable electronic devices, industrial and commercial energy storage, etc. due to their advantages such as high specific energy, long cycle life, and no memory effect. This system is considered to be one of the most promising electrochemical energy storage technologies, and its development and exploration in a wider range of application scenarios has also attracted attention, such as deep space and cold regions. These application scenarios have put forward requirements for the low-temperature discharge performance of lithium-ion batteries. At present, commercial lithium / sodium-ion secondary batteries can hardly discharge at low temperatures below -40°C, especially at high rates, which limits their application in cold-region energy storage, low-altitude drones, and intelligent equipment. The conductivity of lithium-ion electrolytes decreases at low temperatures, and the electrode kinetics of electrode materials are slow, making it difficult to discharge at low temperatures. In addition, for the electrode itself, during discharge, the active material near the current collector consumes lithium ions, resulting in high electronic conductivity and low ionic conductivity, and the side close to the diaphragm has high ionic conductivity and low electronic conductivity. This imbalance in ion and electron conduction rates also reduces the low-temperature performance of the battery.

[0003] The use of low-temperature electrolytes, low-temperature additives, and nano-electrode materials or porous electrodes have improved the low-temperature performance of batteries. However, the above methods cannot alleviate the imbalance of ion-electron conductivity inside the electrode (especially inside thick electrodes), which makes lithium / ion batteries face the problem of insufficient high-rate discharge at low temperatures, limiting the power performance of the battery pack. It is necessary to balance the ion conductivity and electronic conductivity inside the electrode at low temperatures to realize the capacity of the electrode active material, so as to achieve the effect of high-rate discharge and extremely low-temperature discharge of the battery, and promote its application in my country's high-altitude and cold regions. Summary of the invention

[0004] In order to solve the problem of insufficient discharge capacity due to ion-electron imbalance near the current collector inside the electrode of a low-temperature lithium-ion battery, the present invention provides a method for preparing a composite current collector for a low-temperature lithium-ion battery that can be discharged quickly. The composite current collector prepared by the method comprises a porous polymer intermediate layer, and aluminum metal layers or copper layers are plated on both sides, which are used for the positive electrode and the negative electrode respectively. This porous current collector replaces the traditional metal current collector and can absorb and store a certain amount of electrolyte, thereby providing an ion source on one side of the current collector to achieve ion-electron balance, and achieve the effect of high discharge capacity of the battery at low temperature and high current.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] A method for preparing a composite current collector for a low-lithium ion battery capable of rapid discharge at low temperature, comprising the following steps:

[0007] Step 1: Preparation of porous polymer substrate:

[0008] Step 1-1, blending precursor No. 1 and precursor No. 2 at a mass ratio of 10-80:10-80, with a total mass of 0.5-5 g, adding into 20-60 ml of reaction solvent No. 1, and stirring at a speed of 300-1500 r / min for 30-90 min;

[0009] Step 1-2, naturally volatilize the solvent, place it in a vacuum condition at 30-90°C and dry it for 5-24 hours to obtain a powdery substance;

[0010] Step 1-3, adding the powdered substance and precursor No. 3 at a mass ratio of 10-80:10-80 and a total mass of 1-10 g to 20-60 ml of reaction solvent No. 2, stirring at a speed of 300-1500 r / min and 30-90° C. for 30-90 min to obtain a uniform polymer solution;

[0011] Step 1-4, placing the polymer solution in an electrospinning device, spraying it out to form polymer-based fiber filaments with a diameter of 10 to 25 μm, and then weaving them into a three-dimensional mesh porous polymer substrate as a substrate for preparing a composite current collector;

[0012] In this step, Precursor No. 1, Precursor No. 2 and Precursor No. 3 are selected from three of methyl polyethylene glycol methacrylate, methyl acrylate, 2-isocyanatoethyl methacrylate, pentaerythritol tetraacrylate, pentaerythritol tetrakis(3-mercaptopropionic acid), acrylonitrile, polyethylene glycol diacrylate and methyl methacrylate;

[0013] In this step, the mixture is stirred at a speed of 500 to 2000 r / min and irradiated with 100 to 2000 W ultraviolet light for 5 to 60 minutes;

[0014] In this step, reaction solvent No. 1 and reaction solvent No. 2 are selected from two of tetrahydrofuran, NMP, acetone, isopropanol, and ethanol;

[0015] Step 2: Preparation of metal-based prepreg:

[0016] Step 2-1, adding 5 to 20 mg of nano-sized metal particles into reaction solvent No. 3, and stirring at a speed of 300 to 1800 r / min for 0.5 to 6 h;

[0017] Step 2-2, add 0.2-0.8 mg of surfactant, and continue stirring at a speed of 500-1500 r / min for 0.5-6 h;

[0018] Step 2-3, transferring the mixture obtained in step 2-2 to an ultrasonic machine, treating it at a power of 200 to 1600 W for 0.5 to 10 hours to obtain a metal-based prepreg solution;

[0019] In this step, the nano-scale metal particles are one of nano-silver particles, nano-palladium particles, nano-zinc particles, nano-gold particles, nano-iron particles, and nano-platinum particles with a diameter of 50 to 100 nm;

[0020] In this step, the reaction solvent No. 3 is one of water, isopropanol, ethanol, methanol, n-butanol, ethylene glycol, acetone, and toluene;

[0021] In this step, the surfactant is one of polyethylene glycol 600, polyethylene glycol 400, and sodium dodecylbenzene sulfonate;

[0022] Step 3: Preparation of porous composite metal current collector:

[0023] Step 3-1, immersing the porous polymer substrate in a metal-based prepreg solution so that the surface of the porous polymer substrate is covered with conductive metal particles;

[0024] Step 3-2, prepare copper electroplating solution: add copper ion source, accelerator, inhibitor, and leveler into water, and the concentrations thereof are 10-80 g / L, 1-5 mL / L, 0.5-8 mL / L, and 1-10 mL / L, respectively;

[0025] Step 3-3: immerse the porous composite polymer substrate covered with conductive metal particles in a copper electroplating solution, connect a power source, and conduct electricity at a constant temperature of 25°C at a rate of 0.1 to 0.24 A / dm 2 Electroplating is performed at a current density of 20 to 100 s to obtain a porous composite copper current collector;

[0026] Step 3-4, placing the porous composite polymer substrate covered with conductive metal particles on the surface in a magnetron sputtering apparatus, adjusting the target material to an aluminum source, and sputtering at a voltage of 20 to 500 keV to obtain a porous composite aluminum current collector;

[0027] In this step, the accelerator is one of sodium dimethyldithiocarboxamide propane sulfonate (DPS), sodium 3-mercapto-1-propane sulfonate (MPS), and sodium polydisulfide propane sulfonate (SPS);

[0028] In this step, the inhibitor is one of polyether and polyol compounds;

[0029] In this step, the leveling agent is one of polyethyleneimine salts, EO-PO quaternary ammonium salts, polyethyleneimine quaternary ammonium salts, and polyamine substances.

[0030] Compared with the prior art, the present invention has the following advantages:

[0031] 1. The porous composite current collector prepared by the present invention has the function of infiltrating the electrolyte, so there is a sufficient ion source on the side close to the current collector. Compared with the conventional current collector, the porous composite current collector prepared by the present invention has lower internal resistance and high rate discharge performance at low temperature.

[0032] 2. The porous composite current collector prepared by the present invention is lighter than conventional metal current collectors, which is beneficial to lightweight batteries and realizes batteries with higher energy density.

[0033] 3. The porous composite current collector prepared by the present invention has the ability to store electrolyte, thus alleviating the attenuation caused by electrolyte drying up and extending the battery life. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Schematic diagram of the preparation process of porous composite metal current collector;

[0035] Figure 2 This is a scanning electron microscope image of a porous composite metal current collector;

[0036] Figure 3 These are the high-rate discharge curves of conventional batteries and batteries using composite metal current collectors at low temperatures. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below in conjunction with the accompanying drawings, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0038] Embodiment 1:

[0039] This embodiment provides a method for preparing a porous current collector capable of achieving low-temperature and high-power discharge of a lithium-ion battery. Figure 1 As shown, the method comprises the following steps:

[0040] Step 1-1, methyl polyethylene glycol methacrylate and methyl acrylate were blended in a mass ratio of 10:30, with a total mass of 3 g, added into 40 ml of NMP, stirred at a speed of 1000 r / min for 60 min, and irradiated with 1500 W ultraviolet light for 20 min;

[0041] Step 1-2, naturally volatilize the solvent, place it in a vacuum oven at 80°C for 12 hours to obtain a powdery substance;

[0042] Step 1-3, adding the powdered substance and 2-isocyanatoethyl methacrylate in a mass ratio of 30:10 with a total mass of 4 g into 30 ml of acetone, stirring at a speed of 1000 r / min and 70° C. for 60 min to obtain a uniform polymer solution;

[0043] Step 1-4: Place the polymer solution in an electrospinning device and spray it out to form polymer-based fiber filaments with a diameter of 10 μm, which are then woven into a three-dimensional mesh-like porous polymer substrate as a substrate for preparing a composite current collector.

[0044] Step 2: Preparation of metal-based prepreg:

[0045] Step 2-1, add 8 mg of nanosilver particles with a diameter of 50 nm into water and stir at a speed of 1200 r / min for 2 h;

[0046] Step 2-2, add 0.3 mg sodium dodecylbenzene sulfonate, and continue stirring at a speed of 1000 r / min for 3 h;

[0047] Step 2-3: Transfer the mixture obtained in step 2-2 to an ultrasonic machine and treat it at a power of 800 W for 2 hours to obtain a metal-based prepreg solution.

[0048] Step 3: Preparation of porous composite metal current collector:

[0049] Step 3-1, immersing the porous polymer substrate in a metal-based prepreg solution so that the surface of the porous polymer substrate is covered with conductive metal particles;

[0050] Step 3-2, prepare copper electroplating solution: add copper ion source, sodium dimethyldithiocarboxamide propane sulfonate (DPS), propylene oxide, polyethyleneimine into water, and the concentrations thereof are 50 g / L, 2 mL / L, 2.5 mL / L, and 3 mL / L, respectively;

[0051] Step 3-3: immerse the porous composite polymer substrate covered with conductive metal particles in a copper electroplating solution, connect a power source, and conduct electricity at a constant temperature of 25°C at a rate of 0.15A / dm 2 Electroplating was performed for 50 s at a current density of , to obtain a porous composite copper current collector;

[0052] Step 3-4: Place the porous composite polymer substrate covered with conductive metal particles in a magnetron sputtering apparatus, adjust the target material to an aluminum source, and sputter at a voltage of 200 keV to obtain a porous composite aluminum current collector having a morphology as shown in FIG. Figure 2 shown.

[0053] The porous composite metal current collector prepared in the above steps can be used in the positive and negative current collectors of lithium ion batteries or sodium ion batteries. The specific application method is as follows:

[0054] (1) The positive electrode active material, the electronic conductive material, the binder and the solvent of the battery are mixed in a mass ratio of 97:1.5:1.5:120. Similarly, the negative electrode active material, the electronic conductive material, the binder and the solvent of the battery are mixed in a mass ratio of 92:3.5:4.5:120. The mixture is mixed in a planetary agitator for 30 minutes at a speed of 1000 r / min to obtain positive electrode slurry and negative electrode slurry, respectively. The battery active material is lithium nickel cobalt manganese oxide (NCM811), the negative electrode material is spherical graphite, the electronic conductive material is carbon nanotubes, and the binder is PVDF.

[0055] (2) The positive electrode slurry of the battery is coated on the porous aluminum current collector, and the negative electrode slurry is coated on the surface of the porous copper current collector, dried and rolled, and the battery is assembled and tested. As shown in Table 1, compared with the conventional current collector, the battery using the porous current collector has a lower internal resistance at low temperature.

[0056] Table 1

[0057]

[0058] Embodiment 2:

[0059] This embodiment provides a method for preparing a porous current collector capable of achieving low-temperature and high-power discharge of a lithium-ion battery. Figure 1 As shown, the method comprises the following steps:

[0060] Step 1-1, methyl polyethylene glycol methacrylate and methyl acrylate were blended in a mass ratio of 10:30, with a total mass of 5 g, added into 40 ml of NMP, stirred at a speed of 1000 r / min for 60 min, and irradiated with 1500 W ultraviolet light for 20 min;

[0061] Step 1-2, naturally volatilize the solvent, place it in a vacuum oven at 80°C for 12 hours to obtain a powdery substance;

[0062] Step 1-3, adding the powdered substance and 2-isocyanatoethyl methacrylate in a mass ratio of 30:10 with a total mass of 4 g into 30 ml of acetone, stirring at a speed of 1000 r / min and 70° C. for 60 min to obtain a uniform polymer solution;

[0063] Step 1-4: Place the polymer solution in an electrospinning device and spray it out to form polymer-based fiber filaments with a diameter of 10 μm, which are then woven into a three-dimensional mesh-like porous polymer substrate as a substrate for preparing a composite current collector.

[0064] Step 2: Preparation of metal-based prepreg:

[0065] Step 2-1, add 5 mg of nano zinc particles with a diameter of 80 nm into water and stir at a speed of 1200 r / min for 2 h;

[0066] Step 2-2, add 0.3 mg sodium dodecylbenzene sulfonate, and continue stirring at a speed of 1500 r / min for 2 h;

[0067] Step 2-3: Transfer the mixture obtained in step 2-2 to an ultrasonic machine and treat it at a power of 800 W for 2 hours to obtain a metal-based prepreg solution.

[0068] Step 3: Preparation of porous composite metal current collector:

[0069] Step 3-1, immersing the porous polymer substrate in a metal-based prepreg solution so that the surface of the porous polymer substrate is covered with conductive metal particles;

[0070] Step 3-2, prepare copper electroplating solution: add copper ion source, sodium dimethyldithiocarboxamide propane sulfonate (DPS), propylene oxide, polyethyleneimine into water, and the concentrations thereof are 50 g / L, 2 mL / L, 2.5 mL / L, and 3 mL / L, respectively;

[0071] Step 3-3: immerse the porous composite polymer substrate covered with conductive metal particles in a copper electroplating solution, connect a power source, and conduct electricity at a constant temperature of 25°C at a rate of 0.20A / dm 2 Electroplating was performed for 30 s at a current density of , to obtain a porous composite copper current collector;

[0072] Step 3-4: Place the porous composite polymer substrate covered with conductive metal particles in a magnetron sputtering apparatus, adjust the target material to an aluminum source, and sputter at a voltage of 200 keV to obtain a porous composite aluminum current collector, the morphology of which is as follows: Figure 2 shown.

[0073] The porous composite metal current collector prepared in the above steps can be used in the positive and negative current collectors of lithium ion batteries or sodium ion batteries. The specific application method is as follows:

[0074] (1) The positive electrode active material, the electronic conductive material, the binder and the solvent of the battery are mixed in a mass ratio of 96.5:2:1.5:120. Similarly, the negative electrode active material, the electronic conductive material, the binder and the solvent of the battery are mixed in a mass ratio of 92:3.5:4.5:120. The mixture is mixed in a planetary agitator for 30 minutes at a speed of 1000 r / min to obtain positive electrode slurry and negative electrode slurry, respectively. The battery active material is lithium cobalt oxide, the negative electrode material is flake graphite, the electronic conductive material is carbon nanotubes, and the binder is PVDF.

[0075] (2) Apply the positive electrode slurry to the porous aluminum current collector and the negative electrode slurry to the porous copper current collector, dry and roll, assemble the battery, and test it. Figure 3 As shown in Figure 3, compared with conventional current collectors, the battery using porous current collectors has a higher capacity at 5 C discharge at low temperature.

[0076] Embodiment 3:

[0077] This embodiment provides a method for preparing a porous current collector capable of achieving low-temperature and high-power discharge of a lithium-ion battery. Figure 1 As shown, the method comprises the following steps:

[0078] Step 1-1, pentaerythritol tetraacrylate and pentaerythritol tetrakis(3-mercaptopropionic acid) ester were blended in a mass ratio of 15:35, with a total mass of 4.5 g, added into 40 ml of NMP, stirred at a speed of 1000 r / min for 60 min, and irradiated with 1500 W ultraviolet light for 20 min;

[0079] Step 1-2, naturally volatilize the solvent, place it in a vacuum oven at 80°C for 12 hours to obtain a powdery substance;

[0080] Step 1-3, adding the powdered substance and methyl polyethylene glycol methacrylate in a mass ratio of 30:12 with a total mass of 4 g into 30 ml of acetone, stirring at a speed of 1000 r / min and 70° C. for 60 min to obtain a uniform polymer solution;

[0081] Step 1-4: Place the polymer solution in an electrospinning device and spray it out to form polymer-based fiber filaments with a diameter of 15 μm, which are then woven into a three-dimensional mesh-like porous polymer substrate as a substrate for preparing a composite current collector.

[0082] Step 2: Preparation of metal-based prepreg:

[0083] Step 2-1, add 5 mg of nano zinc particles with a diameter of 80 nm into water and stir at a speed of 1200 r / min for 2 h;

[0084] Step 2-2, add 0.3 mg sodium dodecylbenzene sulfonate, and continue stirring at a speed of 1500 r / min for 2 h;

[0085] Step 2-3: Transfer the mixture obtained in step 2-2 to an ultrasonic machine and treat it at a power of 800 W for 2 hours to obtain a metal-based prepreg solution.

[0086] Step 3: Preparation of porous composite metal current collector:

[0087] Step 3-1, immersing the porous polymer substrate in a metal-based prepreg solution so that the surface of the porous polymer substrate is covered with conductive metal particles;

[0088] Step 3-2, prepare copper electroplating solution: add copper ion source, sodium dimethyldithiocarboxamide propane sulfonate (DPS), propylene oxide, polyethyleneimine into water, and the concentrations thereof are 50 g / L, 2 mL / L, 2.5 mL / L, and 3 mL / L, respectively;

[0089] Step 3-3: immerse the porous composite polymer substrate covered with conductive metal particles in a copper electroplating solution, connect a power source, and conduct electricity at a constant temperature of 25°C at a rate of 0.20A / dm 2 Electroplating was performed for 30 s at a current density of , to obtain a porous composite copper current collector;

[0090] Step 3-4: Place the porous composite polymer substrate covered with conductive metal particles in a magnetron sputtering apparatus, adjust the target material to an aluminum source, and sputter at a voltage of 200 keV to obtain a porous composite aluminum current collector, the morphology of which is as follows: Figure 2 shown.

[0091] The porous composite metal current collector prepared in the above steps can be used in the positive and negative current collectors of lithium ion batteries or sodium ion batteries. The specific application method is as follows:

[0092] (1) The positive electrode active material, the electronic conductive material, the binder and the solvent of the battery are mixed in a mass ratio of 96.5:2:1.5:120. Similarly, the negative electrode active material, the electronic conductive material, the binder and the solvent of the battery are mixed in a mass ratio of 92:3.5:4.5:120. The mixture is mixed in a planetary agitator for 30 minutes at a speed of 1000 r / min to obtain positive electrode slurry and negative electrode slurry, respectively. The battery active material is lithium cobalt oxide, the negative electrode material is flake graphite, the electronic conductive material is carbon nanotubes, and the binder is PVDF.

[0093] (2) The positive electrode slurry of the battery is coated on the porous aluminum current collector, and the negative electrode slurry is coated on the surface of the porous copper current collector, and then dried and rolled to assemble the battery.

[0094] Embodiment 4:

[0095] The difference between this embodiment and embodiment 1 is that the reaction solvent No. 1 and the reaction solvent No. 2 are replaced with isopropanol and ethanol, and the same effect can be achieved.

Claims

1. A method for preparing a composite current collector for a low-lithium ion battery capable of rapid discharge at low temperature, characterized in that The method comprises the following steps: Step 1: Preparation of porous polymer substrate: Step 1-1, blending precursor No. 1 and precursor No. 2 at a mass ratio of 10-80:10-80, with a total mass of 0.5-5 g, adding into 20-60 ml of reaction solvent No. 1, and stirring at a speed of 300-1500 r / min for 30-90 min; Step 1-2, naturally volatilize the solvent, place it in a vacuum condition at 30-90°C and dry it for 5-24 hours to obtain a powdery substance; Step 1-3, adding the powdered substance and precursor No. 3 at a mass ratio of 10-80:10-80 and a total mass of 1-10 g to 20-60 ml of reaction solvent No. 2, stirring at a speed of 300-1500 r / min and 30-90° C. for 30-90 min to obtain a uniform polymer solution; Step 1-4, placing the polymer solution in an electrospinning device, spraying it out to form polymer-based fiber filaments, and then weaving them into a three-dimensional mesh-like porous polymer substrate; The precursor No. 1, the precursor No. 2 and the precursor No. 3 are selected from three of methyl polyethylene glycol methacrylate, methyl acrylate, 2-isocyanoethyl methacrylate, pentaerythritol tetraacrylate, pentaerythritol tetrakis (3-mercaptopropionic acid), acrylonitrile, polyethylene glycol diacrylate and methyl methacrylate; Step 2: Preparation of metal-based prepreg: Step 2-1, adding 5 to 20 mg of nano-sized metal particles into reaction solvent No. 3, and stirring at a speed of 300 to 1800 r / min for 0.5 to 6 h; Step 2-2, add 0.3-0.8 mg of surfactant, and continue stirring at a speed of 500-1500 r / min for 0.5-6 h; Step 2-3, transferring the mixture obtained in step 2-2 to an ultrasonic machine, treating it at a power of 200 to 1600 W for 0.5 to 10 hours to obtain a metal-based prepreg solution; Step 3: Preparation of porous composite metal current collector: Step 3-1, immersing the porous polymer substrate in a metal-based pre-impregnation solution so that the surface of the porous polymer substrate is covered with conductive metal particles; Step 3-2, prepare copper electroplating solution: add copper ion source, accelerator, inhibitor, and leveler into water, and the concentrations thereof are 10-80 g / L, 1-5 mL / L, 0.5-8 mL / L, and 1-10 mL / L, respectively; Step 3-3: immerse the porous composite polymer substrate covered with conductive metal particles in a copper electroplating solution, connect a power source, and conduct electricity at a constant temperature of 25°C at a rate of 0.1 to 0.24 A / dm 2 Electroplating was carried out at a current density of 20 to 100 s to obtain a porous composite copper current collector.

2. The method for preparing a composite current collector for a low-lithium ion battery capable of rapid discharge at low temperature according to claim 1, characterized in that In the step 1, the mixture is stirred at a speed of 500 to 2000 r / min and irradiated with ultraviolet light of 100 to 2000 W for 5 to 60 minutes.

3. The method for preparing a composite current collector for a low-lithium ion battery capable of rapid discharge at low temperature according to claim 1, characterized in that In the step 1, reaction solvent No. 1 and reaction solvent No. 2 are selected from two of tetrahydrofuran, NMP, acetone, isopropanol, and ethanol; and the nano-scale metal particles are one of nano-silver particles, nano-palladium particles, nano-zinc particles, nano-gold particles, nano-iron particles, and nano-platinum particles.

4. The method for preparing a composite current collector for a low-lithium ion battery capable of rapid discharge at low temperature according to claim 1 or 3, characterized in that The diameter of the nano-scale metal particles is 50-100 nm.

5. The method for preparing a composite current collector for a low-lithium ion battery capable of rapid discharge at low temperature according to claim 1, characterized in that In the step 1, the diameter of the polymer-based fiber filament is 10 to 25 μm.

6. The method for preparing a composite current collector for a low-lithium ion battery capable of rapid discharge at low temperature according to claim 1, characterized in that In step 2, reaction solvent No. 3 is one of water, isopropanol, ethanol, methanol, n-butanol, ethylene glycol, acetone, and toluene; and the surfactant is one of polyethylene glycol 600, polyethylene glycol 400, and sodium dodecylbenzene sulfonate.

7. The method for preparing a composite current collector for a low-lithium ion battery capable of rapid discharge at low temperature according to claim 1, characterized in that In step 3, the accelerator is one of sodium dimethyl dithiocarboxamide propane sulfonate, sodium 3-mercapto-1-propane sulfonate, and sodium polydisulfide propane sulfonate; the inhibitor is one of polyether and polyol compounds; and the leveler is one of polyethyleneimine salts, EO-PO quaternary ammonium salts, polyethyleneimine quaternary ammonium salts, and polyamine substances.

8. The method for preparing a composite current collector for a low-lithium ion battery capable of rapid discharge at low temperature according to claim 1, characterized in that The step 3-3 is replaced by: placing a porous composite polymer substrate with conductive metal particles on its surface in a magnetron sputtering apparatus, adjusting the target material to an aluminum source, and sputtering at a voltage of 20 to 500 keV to obtain a porous composite aluminum current collector.

9. Use of a composite current collector prepared by the method according to any one of claims 1 to 8 in a lithium ion battery or a sodium ion battery.

Citation Information

Patent Citations

  • Preparation method of lithium ion battery based on three-dimensional net-shaped copper current collector

    CN109817986A

  • Preparation method of lithium ion battery based on porous copper current collector

    CN109817988A

  • Composite current collector, preparation method and application thereof

    CN112201792A

  • Lightweight 3D current collector composite material and preparation method and application thereof

    CN115347189A

  • Current collector, battery and processing method of current collector

    CN116264281A